Emergency Department Visits After Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis. Issue 7 (August 2020) - Harris, Andrew B.; Marrache, Majd; Puvanesarajah, Varun; Raad, Micheal; Skolasky, Richard L.; Njoku, Dolores; Sponseller, Paul D.; Jain, Amit
Abstract : Background: The incidence of emergency department (ED) visits after posterior spinal fusion (PSF) in adolescent idiopathic scoliosis (AIS) patients is not well known. We hypothesize that the majority of ED visits are related to constipation and pain issues, and are not for serious complications. Methods: Using a private insurance claims database, we identified AIS patients aged 10 to 21 years who underwent PSF from 2010 to 2015. Patients were excluded for diagnoses of neuromuscular or syndromic scoliosis. ED visits that occurred within the 6-month postoperative period were identified. The diagnoses present at these visits were pooled and analyzed, in addition to insurance payments associated with these visits. Significance was set at P =0.05. Results: A total of 5934 patients met inclusion criteria. Mean age was 14.4±2.2 years, and 75% of the patients were girls. A total of 577 (9.7%) patients had at least 1 ED visit in the 6-month postoperative period, whereas 92 (1.6%) had 2 ED visits and 19 (0.3%) had 3 or more ED visits. The median time to ED visits was 33 days after surgery. Independent risk factors for ED visits were: older age, and greater levels fused ( P <0.05). The top 5 most common reasons for ED visits were: pain/back or musculoskeletal, constipation/GI issues, asthma/ respiratory issues, upper respiratory infection, and dehydration. Rates of ED visits were similar among the US geographic regions. Patients who had an ED visit had significantly higher total 6-month health care payments than those who did not ( P <0.001). Conclusions: Approximately 10% of the patients had ≥1 ED visit in the 6-month period after PSF for AIS. A majority of the diagnoses at these ED visits were outpatient medical issues. Level of Evidence: Level III.